The second summer of the sisterhood - Brashares, Ann. (New York : Delacorte Press, 2004)
A sequel to "The Sisterhood of the Traveling Pants" in which the four girls, now sixteen, embark on another summer of travels and life lessons charmed by a shared pair of seemingly magical thrift-store jeans.
"Readers circle"--Cover.
Books for the Teen Age (NYPL)
School Library Journal
Wilson's Senior High School
5.5
Young Adult
Keywords: Friendship -- Fiction; Girls -- Fiction; Jeans (Clothing) -- Fiction; Summer -- Fiction; Friendship -- Fiction; Girls -- Fiction; Jeans (Clothing) -- Fiction; Summer -- Fiction